Φωτοβολταϊκή Τεχνολογία Οργανικών Ημιαγωγών: Μελέτη Καινοτόμων Οργανικών Ηλιακών Κυψελών Φθαλοκυανίνης Μολύβδου (PbPc) σε υποστρώματα GaAs με επιφανειακές αναδομήσεις β2(2x4) και c(4x4) - Ρούσση, Κωνσταντίνα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών. Τομέας Φυσικής, 2014)
In this work, organic solar cells based on lead phthalocyanine (PbPc) grown on two different surface reconstructed Gallium Arsenide substrates GaAs(001), As‐rich c(4x4) and stoichiometric β2(2x4), were structurally and electrically characterized. The PbPc‐GaAs(001) c(4x4) and PbPc‐GaAs(001) β2(2x4) bilayers were grown by Dr. P. Vogt (Workgroup Prof. Dr. M. Kneissl) at the Technical University of Berlin. PbPc is an organic molecule with very good optoelectronic properties promising to be used in organic thin film solar cells or combination of organic and inorganic thin film solar cells. Different substrates are exploited, because changes in the behavior of phthalocyanines and different molecule qualities have been reported in dependence of the substrate surface‐structure. In particular, PbPc belongs to the category of metal phthalocyanines that change their molecular ranking when they are deposited on different substrates by taking the orientation of the substrate surface‐reconstruction, which means that they change their absorption properties. The experimental research and the results we gain can show us, which sample is efficient in absorbing solar radiation and can thus be used as solar energy converter. Understanding the material properties is important for potential applications and improvements in view of their use as molecular solar cells and their use as thin film interlayer to improve the electronic properties of optoelectronic devices. It is also important to study the interaction between the molecules and the substrate as this interaction can be strong, leading to the formation of chemical bonds between them. This interaction can also alter the chemical bonds of the molecules and, therefore, their structure. For this reason, the growth (usually epitaxial) of organic molecules on inorganic substrates is an actual and intensive research topic. The electrical conductivity of lead phthalocyanine (PbPc), studied in this work, and that of metal phthalocyanines, in general, depends on the orientation of the molecules. Many parameters are important to consider for the orientation and the arrangement of the organic molecules in a layer, but the research is focused on the interaction of the organic layer with the substrate and the arrangements of the organic molecules in the first monolayer of the interface of the organic layer‐substrate (inorganic–bio mainly). RAMAN Spectroscopy has been applied for the structural characterization of PbPc on GaAs substates within this diploma‐thesis. Since PbPc was deposited on GaAs substates from the vapor phase, the Raman spectrum of PbPc in‐vapor‐phase has been studied. In these experiments, the organic molecules are formed following the crystalline ordering of the substrates they lay on. Raman scattering is a non‐invasive experimental method that detects the vibration of a molecule and identifies its characteristic spectral pattern (fingerprint). Samples can be examined in the solid‐, liquid‐ or vapor‐phase, in hot or cold states, in the bulk, as microscopic particles, and as surface layers. The sample used for the Raman study was powder of lead phthalocyanine in glass container that was heated to produce PbPc free molecules in vapor phase. The study of PbPc in vapor phase was important as PbPc in the electrically characterized solar cells was deposited after being vaporized. The information of structural characterization of PbPc in vapor phase that is given by its Raman spectrum is considerable, since it provides us with information before the electrical characterization of the solar cells (PbPc on GaAs substrates). The spectral pattern of PbPc in vapor phase was initially recorded and the vibration modes of PbPc free molecules were extensively analyzed and presented within the frame of the doctoral thesis of L. Riele. Assignment of the vibrational modes of PbPc powder was then at that time already known, since it has been reported by Dr. V. Stamelou in her doctoral thesis. Apart from the experimental work referred, there are theoretical calculations of density functional theory (DFT) on the mode vibrations of PbPc molecules published by Yuexing Zhang and Xianxi Zhang and by I.M. Kupchak which seem to be in agreement, when referring to mode vibrations and mode frequencies. In the present diploma thesis, the Raman spectrum of PbPc in‐vapor phase has been re‐ evaluated. Mode vibrations have been re‐assigned by taking into account theoretical and experimental results known from the Literature. This new interpretation is in accordance with the results of DFT calculations and the Raman analysis of PbPc powder in Refs. L. Riele and V. Stamelou. For PbPc in‐vapor, however, a mode‐shift has been added in the evaluation of Raman‐spectra by L. Riele to account for additional motion (degrees of freedom) of vaporized molecules. On the contrary, the present evaluation is based on the fact that the molecule vibrations are drastically constrained by the presence of the heavy metal atom. Bearing in mind that the protruding lead cation (Pb2+) is responsible for the spatial distribution and the asymmetry of the molecule, it is assumed that it is also, to a great extend, responsible for the molecule vibrations and that mode‐ frequencies are not significantly altered in both, the solid (PbPc powder) and the vapor phase (PbPc in vapor). In the following, the I‐V characteristics of PbPc‐GaAs(001) c(4x4) and PbPc‐GaAs(001) β2(2x4) solar cells and the Raman‐spectrum of PbPc in‐vapor‐phase, as “start” material for the solar absorber, will be presented and discussed inclusive the basic principles of operation of photovoltaic cells and the principles of Raman scattering as the main material characterization technique. In addition, the instrumentation of the laboratory will be presented in the Experimental part so far it has been used in the referred experimental measurements.